2022
DOI: 10.47405/mjssh.v7i1.1224
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Mental Health Among Malaysian University Students During Covid-19 Pandemic

Abstract: The COVID-19 pandemic and the lockdown have led to an increasing number of mental health issues in Malaysia. The demands of living during the pandemic have caused a rising number of university students to be diagnosed with depression, anxiety, stress and other mental health problems. A survey done by National Health and Morbidity 2015 found that the prevalence of mental health problems among adults in Malaysia has increased from 10.7% in 1996, to 11.2% in 2006, to 29.2% in 2015. Moreover, one in 10 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Several stressors, including financial difficulties, online classes, and inaccurate news on social media, have been identified as important factors affecting students' mental well-being. Other stressors include poor internet connection, extended class hours, high expectations from their lecturer, a decline in social interactions, and the uncertainty of their future career and life plans, which have further contributed to mental stress and other health issues [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Several stressors, including financial difficulties, online classes, and inaccurate news on social media, have been identified as important factors affecting students' mental well-being. Other stressors include poor internet connection, extended class hours, high expectations from their lecturer, a decline in social interactions, and the uncertainty of their future career and life plans, which have further contributed to mental stress and other health issues [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if students are unable to cope with their stressful situations and leave the stressful state untreated, it may result in unfavorable mental health outcomes, increased morbidity, and could potentially have adverse consequences on both their professional and personal lives. The probable explanations could be the students are less tolerant of situations where they are unable to control and cope with the stressful environment ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salim, 2010;Azizan et al, 2013;Khan et al, 2010). Recently, a study among Malaysian university students depicts that the majority of the respondents experienced depression by having negative feelings, feeling anxious and stressed, experiencing mouth dryness, and finding it difficult to become enthusiastic (Hassan et al, 2022). Meanwhile, in a study by Kamaluddin et al (2020), around 30% of the university students were reported to experience some level of anxiety due to the COVID-19 pandemic.…”
Section: Problem Statementmentioning
confidence: 99%
“…According to Hassan et al (2022), this is a serious problem because persistent psychological distress can impair students' academic achievements and their well-being life in overall. The depression, anxiety and any kind of stressful symptoms experienced by university students must be given greater attention and immediate treatment.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation